A Critical Review of the Schedules of the Wildlife (Protection) Act, 1972 and their Amendments - Bisht, S. S. (Indian Forester, 1999)
The Wildlife (Protection) Act, 1972 provides protection to different species of wild animals and plants by assigning them to six schedules, each enjoying a different level oflegal protection. Non-inclusion or wrong inclusion of a species in the schedules may have an adverse impact on its future. Efficient implementation of the Act depends upon a careful organisation and management of the schedules. In the original Act the schedules were organised on the basis of the importance enjoyed by various species as 'Game'. But four amendments later, the schedules have lost their direction and thrust. The amendments in the schedules have not followed any criteria and resulted in making the schedules unwieldy and unstable. The schedules do not bear scrutiny with regard to their coverage of biodiversity or representation of threatened species. There are also contradictions between the schedules and the appendices of the CITES and the Export Policy of h~dia. The schedules also suffer from a number of taxonomic defects. Some suggestions for improving the organisation and management of the schedules have been made in this paper.